2010
DOI: 10.1088/0953-8984/22/30/304009
|View full text |Cite
|
Sign up to set email alerts
|

Surface structure of niobium-doped potassium tantalate KTa1 −xNbxO3obtained from helium atom scattering studies

Abstract: Helium atom scattering experiments have been carried out on the (001) surface of KTaO(3) doped with 6, 10 and 15% Nb, produced by cleaving in situ single crystal samples. Several phenomena were observed through He atom diffraction measurements, including metastable behavior immediately after cleaving, reconstruction of a fraction of the surface to (2 × 1) domains after thermally cycling the surface temperatures, and the distribution of step heights of terraces at the surface as multiples of the unit cell dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…In all cases for targets with Nb doping levels up to 20%, the Fourier transform of the oscillations in the specular peak intensities revealed that the principal step height between terraces was 4 Å. [7][8][9][10] A step height of 8 Å was also seen in almost all experiments, but with a much smaller probability. A step height of 6 Å with even lower probability was found in only a few experiments.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…In all cases for targets with Nb doping levels up to 20%, the Fourier transform of the oscillations in the specular peak intensities revealed that the principal step height between terraces was 4 Å. [7][8][9][10] A step height of 8 Å was also seen in almost all experiments, but with a much smaller probability. A step height of 6 Å with even lower probability was found in only a few experiments.…”
mentioning
confidence: 88%
“…[5] The helium atom scattering (HAS) laboratory group at FSU has investigated cleaved (001) perovskite surfaces, particularly potassium tantalate (KTaO 3 ) [6], and potassium tantalate doped with Nb (KTN) [7][8][9] or lithium (KLT). [9,10] When cleaved, the fresh surfaces are nominally composed of layers, KO/LiO and TaO 2 /NbO 2 , that are formally charged -1 and +1, respectively.…”
mentioning
confidence: 99%
See 3 more Smart Citations